Mysticism beyond time A comparative study of traditional vs. modern mysticism - Szugyiczki Zsuzsanna (2023)
Mysticism in modernity is often described as ‘muddled’ and ‘superficial’ in contemporary research. These negative connotations are especially outstanding when modern mysticism is compared to a ‘classical’ or ‘traditional’ version of mysticism. On this basis, it would seem that modern phenomena do not meet the high standards that scholars attribute to the traditional versions of mysticism and on which most definitions of mysticism are based. Therefore, in this dissertation, I argue that (1) we can characterize mysticism as traditional and modern mysticism based on contemporary theoretical works. (2) The differences that these categories are based on apply only to the contextual elements of mysticism, not to mystical experiences. (3) As this differentiation does not apply to mystical experiences, modern mysticism is essentially the same as traditional mysticism. (4) Modern mysticism lacks sufficient theoretical explanations. (5) Due to contextual changes related to modern mysticism, mysticism requires an updated theoretical account in terms of its definition and categories.